Saberes sobre as práticas de caça no quilombo Pedro Cubas, Vale do Ribeira, SP - Olegário, Manoela (2023)
Traditional communities are constantly harmed by the western common sense regarding their subsistence activities and wildlife conservation. Guided by the myth of the "Untouched Nature," they disregard the presence, importance, and participation of these communities in restoration projects and the demarcation of protected areas. Since they are embedded in these contexts, they have a close relationship with biodiversity, offering a perspective rich in ecological knowledge and congruent with academic views. This dissertation conducted unstructured interviews with twelve residents from the communities of Pedro Cubas and Pedro Cubas de Cima (Vale do Ribeira - SP) in the second half of 2021 and the first half of 2022, along with participative observation. The objective was to present the narratives of hunting and fishing and the intrinsic ecological knowledge as fundamental and complementary to wildlife conservation projects. The interviewees were divided into three categories: those who hunt, those who used to hunt but don't anymore, and those who have never hunted. This allowed for a discussion on the inherent knowledge in hunting narratives, the difficulties and challenges of engaging in hunting activities nowadays, as well as the impact of urbanization on the younger generations, which distances them from hunting and other local subsistence activities. Even with the presence of remaining Quilombola populations in Conservation Units, there are still significant discussions about their permanence and importance in wildlife conservation. As a trigger for future projects, the concept of "companion species" was introduced in the results. This work discusses hunting not only as a source of food but also as an element of culture and medicine and its implications in relationships with existing diversity.